2000
DOI: 10.1097/00004647-200005000-00012
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution CMRO2 Mapping in Rat Cortex: A Multiparametric Approach to Calibration of BOLD Image Contrast at 7 Tesla

Abstract: The blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) method, which is sensitive to vascular paramagnetic deoxyhemoglobin, is dependent on regional values of cerebral metabolic rate of oxygen utilization (CMR(O2)), blood flow (CBF), and volume (CBV). Induced changes in deoxyhemoglobin function as an endogenous contrast agent, which in turn affects the transverse relaxation rates of tissue water that can be measured by gradient-echo and spin-echo sequences in BOLD fMRI. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(166 citation statements)
references
References 49 publications
8
158
0
Order By: Relevance
“…This decrease in field-evoked potential is linearly related with the decrease in the evoked CMRO 2 as well as BOLD signal and CBF (Kida et al, 2001(Kida et al, , 2006, consistent with the result that the activation-dependent release of glutamate and the glutamate-glutamine cycles require a proportionate oxidative energy consumption (Sibson et al, 1998). Furthermore, a linear relationship between BOLD signals and oxygen consumption associated with cortical activation produced by either physiological perturbations or forepaw stimulation has been reported (Kida et al, 2000;Sanganahalli et al, 2009;Herman et al, 2009). These findings regarding cerebral oxygen consumption that correlate with both SEP and the BOLD signal support the correlation between BOLD signal and SEP amplitude obtained in the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This decrease in field-evoked potential is linearly related with the decrease in the evoked CMRO 2 as well as BOLD signal and CBF (Kida et al, 2001(Kida et al, , 2006, consistent with the result that the activation-dependent release of glutamate and the glutamate-glutamine cycles require a proportionate oxidative energy consumption (Sibson et al, 1998). Furthermore, a linear relationship between BOLD signals and oxygen consumption associated with cortical activation produced by either physiological perturbations or forepaw stimulation has been reported (Kida et al, 2000;Sanganahalli et al, 2009;Herman et al, 2009). These findings regarding cerebral oxygen consumption that correlate with both SEP and the BOLD signal support the correlation between BOLD signal and SEP amplitude obtained in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Since the T 2 -dependent signal changes are the most sensitive mathematically when the TE is set to the resting T 2 value and the value in the rat somatosensory cortex under deep anesthetic condition like this experiment is 40 ms (Kida et al, 2000), we employed 40 ms for the TE.…”
Section: Fmri Experimentsmentioning
confidence: 99%
“…These results and ours using the spin-echo sequence contradict those using the gradient-echo sequence (Gyngell et al, 1996;Brinker et al, 1999). Several studies have reported that spin-echo sequences with high magnetic field strengths have an advantage over gradient-echo sequences, that is, they allow the observation of local activation Kida et al, 2000;Lee et al, 2002). The BOLD signals obtained using spin-echo sequences represent the following 3 components: (1) extravascular effect of the capillary bed, (2) intravascular effect of both the large and small blood vessels, and (3) absence of the transverse relaxation time (T 2 ) effect such as the inflow effect Lee et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…Since BOLD signals correlate with the deoxygenated hemoglobin content (Ogawa et al, 1990), the stimulus frequency dependence of BOLD signals should correspond to the deoxygenated hemoglobin content assessed by optical imaging, and a similar dependence is expected with regard to changes in the cerebral blood flow (CBF) (Hoge et al, 1999;Kida et al, 2000;Silva et al, 2000). However, conflicting results were obtained with regard to the stimulus frequency dependence of the BOLD signals measured by MRI and the changes in CBF measured using LDF.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the relationship between the cerebral metabolic rate for oxygen consumption (CMRO 2 ), cerebral blood flow (CBF) and blood volume (CBV) using MRI techniques and showed a tight proportionality between fractional changes in CMRO 2 and CBF measured at rest in humans (Hyder et al, 1998) and during graded anesthesia in the rats (Kida et al, 2000). For example, the ratio defined as DCMRO 2 / DCBF (measured during pharmacologic perturbations) in anesthetized rats is approximately 0.8 to 0.9 and can be increased or decreased slightly by assuming alterations of the oxygen diffusivity properties of the capillary bed (Kida et al, 2000).…”
Section: Conclusion and Discussionmentioning
confidence: 99%